From food to vesicle: nutritional influences on gut microbial inflammatory signaling - Verbunt, Jari; Mennens, Lisa; Jocken, Johan; Blaak, Ellen E.; Savelkoul, Paul; Stassen, Frank R. M. (Frontiers in Nutrition, 2026)
Diet is a pivotal determinant of gut microbial ecology, giving not only rise to specific bacterial compositionality but also its functional output. Studying functional readouts—such as microbial metabolite production—could provide a more accurate and mechanistically informative measure of intervention outcome than traditional compositional profiling alone. Bacterial membrane vesicles (bMVs) are gaining attention as mediators of microbial metabolism and output. These nanoparticles are selectively released as carriers of bioactive proteins, lipids, nucleic acids, and metabolites reflective of the activity of the parent bacteria. Importantly, bMVs are rigid, can efficiently be isolated from feces, and are able to stably transport their cargo to interact with the host. In interacting with immune cells or pathogen recognition receptors, they can potentiate inflammatory responses. Given their extensive, multifaceted involvement in inter-Kingdom communication, bMVs represent an important biomarker for evaluating dietary modulation of gut microbial function. We propose that characterization of gut-derived bMVs offers a highly sensitive, mechanistically grounded approach to titrating impact of dietary interventions. By capturing shifts in microbial metabolic activity and inflammatory potential, bMV-based assessments could complement or surpass traditional measures of microbiome compositional change. Integrating bMV profiling into dietary intervention studies may therefore provide new insight into the functional consequences of diet–microbiome interactions and help refine strategies aimed at reducing inflammation and promoting host health.